Israel : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix reviews developments in the structure of the Israeli banking sector, as well as in the key indicators of soundness and profitability in recent years. The paper highlights that Israel's financial system continues to be dominated by a small number of banking groups. By international standards, the banking system is highly concentrated, with the largest five banking groups controlling almost 95 percent of total assets. The paper also describes developments in exchange restrictions in Israel.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet